2016
DOI: 10.1002/chem.201601334
|View full text |Cite
|
Sign up to set email alerts
|

Sophisticated Design of Covalent Organic Frameworks with Controllable Bimetallic Docking for a Cascade Reaction

Abstract: Precise control of the number and position of the catalytic metal ions in heterogeneous catalysts remains a big challenge. Here we synthesized a series of two-dimensional (2D) covalent organic frameworks (COFs) containing two different types of nitrogen ligands, namely imine and bipyridine, with controllable contents. For the first time, the selective coordination of the two nitrogen ligands of the 2D COFs to two different metal complexes, chloro(1,5-cyclooctadiene)rhodium(I) (Rh(COD)Cl) and palladium(II) acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 40 publications
5
80
0
4
Order By: Relevance
“…[27] Using a programmed synthetic procedure, two metal complexes, Rh(COD)Cl and Pd(OAc) 2 , with different size can be selectively coordinated with the two nitrogen ligands in the COFs. To show this, a series of 2D COFs containing two different types of nitrogen ligands, namely imine and bipyridine, with controllable content were synthesized by a three-component condensation system.…”
Section: Catalysismentioning
confidence: 99%
“…[27] Using a programmed synthetic procedure, two metal complexes, Rh(COD)Cl and Pd(OAc) 2 , with different size can be selectively coordinated with the two nitrogen ligands in the COFs. To show this, a series of 2D COFs containing two different types of nitrogen ligands, namely imine and bipyridine, with controllable content were synthesized by a three-component condensation system.…”
Section: Catalysismentioning
confidence: 99%
“…[38] Flexible adjustment of the pore size and shape has also been achieved. [39][40][41][42][43] In the case of C 2v -symmetrical building blocks, it was reported that monomers with different spacerl engths led to differentC OF isomers. This means that exact structures of the COFs cannotb ep redicted, and the outcomes of the condensation reactions cannot be precisely controlled to afford COFs with expected frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…PL measurements of the three materials reveal a weak, broad, and structureless excimer emission band around 670-700 nm (see Figure S17b, Supporting Information). [13,14,24,25] From the photoluminescence results, a 6.5 Å shift between adjacent layers seems unlikely (see Section SH, Supporting Information): While pyrene sandwich excimers could well form by a small conformational rearrangement, i.e., a small horizontal slip, upon photoexcitation in the 1.6 Å shifted-AA' stacked system, [26] this is unlikely for large layer offsets such as in the 6.5 Å shifted-AA' stacked system. [14,24] In contrast, the all-planar linkers of the A-TEXPY-COFs lead to a significantly smaller stacking distance of about 3.43 Å (vide supra), hence enabling formation of excimers (see Figure S17b, Supporting Information).…”
Section: Photoluminescence Measurementsmentioning
confidence: 99%